Masculino 43 años. Absceso del Psoas en paciente con Enfermedad de Crohn - Guillén Vindas, Silvia (2012)
Crohn's disease is a chronic entity that belongs to the group of inflammatory bowel diseases. It ́s etiology is unknown, but is believed to be caused by an immune component. Mainly, this disease affects the small intestine, primarily ileum. Among the complications that can occur, with intestinal manifestations of Crohn's disease, are the psoas abscess and intestinal wall. Psoas abscess is a rare condition associated with different entities, whose diagnosis is made by the CAT scan and its treatment involves surgical drainage and antibiotics.